Strategi Transformasi Digital Perguruan Tinggi: Redesain Organisasi Teknologi Informasi - Mohamad Arief Setiawan; Muhammad Rasyid Ridho; Roni Herdianto; Dzikra Syahidin (Belantika Pendidikan, 2026)
Abstract: An effective IT organizational structure is a critical foundation for the success of digital transformation in higher education, yet many institutions still maintain outdated organizational models. This study redesigns the IT organizational structure of a public university (referred to as University X) using an integrated framework combining COBIT 2019, SFIA 8, and IT-CMF v3. A mixed-methods approach was employed through a validated questionnaire (n=47) and interviews with 12 key informants. The COBIT 2019 assessment revealed IT process maturity levels of 2.1 and 1.8, well below the target level of 4. Based on a gap analysis, the study proposes transforming the existing ICT Center into an ICT Institute comprising four functional centers, accompanied by SFIA 8–based competency mapping, validated through a focus group discussion and expert review. The findings confirm that federal/hybrid IT governance with a clear separation of strategic and operational functions enhances governance effectiveness. This study contributes to developing an adaptive model for designing university IT organizations that support digital transformation in developing countries. Abstrak: Struktur organisasi TI yang efektif merupakan fondasi keberhasilan transformasi digital perguruan tinggi, namun banyak institusi masih mempertahankan model organisasi yang usang. Penelitian ini merancang ulang struktur organisasi TI sebuah perguruan tinggi negeri (Universitas X) menggunakan kerangka terpadu COBIT 2019, SFIA 8, dan IT-CMF v3. Pendekatan mixed-methods diterapkan melalui kuesioner tervalidasi (n=47) dan wawancara dengan 12 informan kunci. Asesmen COBIT 2019 menunjukkan kematangan proses TI pada level 2,1 dan 1,8, jauh di bawah target level 4. Berdasarkan gap analysis, penelitian mengusulkan transformasi Pusat TIK menjadi Lembaga TIK dengan empat pusat fungsional, disertai pemetaan kompetensi berbasis SFIA 8, yang divalidasi melalui FGD dan penilaian pakar. Hasil mengonfirmasi bahwa tata kelola TI federal/hybrid dengan pemisahan fungsi strategis dan operasional meningkatkan efektivitas tata kelola. Penelitian ini berkontribusi pada pengembangan model perancangan organisasi TI perguruan tinggi yang adaptif terhadap transformasi digital di negara berkembang.